Teacher's Strategy in Habitualizing Quran Reading and Dhuha Prayer in Shaping Students' Character - Ramadani, Tsulusul Lail (Global Action and Education for Society, 2025)
This study aims to analyse the teacher's strategy in getting used to reading the Qur'an and praying dhuha as an effort to build student character at UPT SDN 357 Gresik. Character education is a fundamental aspect in the national education system that aims not only to improve cognitive competence, but also to form religious values of responsibility and honesty. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results showed that the teacher's strategy in the habituation of reading the Qur'an and praying dhuha had a positive impact on student character, especially in increasing discipline, religion, honesty and responsibility. Teachers apply exemplary, habituation, and motivation approaches to instil this habit, with the support of supervision from the school. Although the programme is effective, there are obstacles in its implementation, such as time constraints and students' lack of seriousness in carrying out the activities. Therefore, more innovative strategies are needed to ensure the sustainability of the programme. Overall, the habituation of reading the Qur'an and praying dhuha proved to be an effective instrument in building better student characters in the school and community environment.